Using Skin Bioengineering to Highlight How Weight and Diabetes Mellitus Modify the Skin in the Lower Limbs of Super-Obese Patients - Iacopi E (Dove Medical Press, 2020)
Elisabetta Iacopi,1 Nicola Riitano,1,2 Valentina Dini,2 Rossana Berta,3 Letizia Pieruzzi,1 Agata Janowska,2 Marco Anselmino,3 Alberto Piaggesi,1 Marco Romanelli2 1Diabetic Foot Section, Pisa University Hospital, Pisa, Italy; 2Dermatology Department, Pisa University Hospital, Pisa, Italy; 3Bariatric Surgery Unit, Pisa University Hospital, Pisa, ItalyCorrespondence: Marco RomanelliDermatology Unit, Via Roma, 67, Pisa 56126, ItalyTel +39 050 992436Fax +39 050 551124Email m.romanelli@med.unipi.itAim: To evaluate the distinct contribution of obesity and diabetes (DM) to the skin modification in metabolic diseases.Methods: We analysed all patients admitted for bariatric surgery in our hospital with BMI between 38 and 47 kg/m2, with (Group 1) or without (Group 2) DM and compared them with a group of nonobese diabetic patients (Group 3) and healthy volunteers (Group 4). The following features were evaluated: hardness, temperature, hydration and thickness alongside with anthropometric measures of foot and leg.Results: For the general characteristics, patients differed in age and body mass index. As predictable all circumferences (dorsal foot, sovramalleolar and under the knee) were significantly higher in obese with no differences depending on DM (all parameters: p< 0.01 in Group 1 and Group 2 vs Group 3 and Group 4). Skin temperature was significantly higher in all obese, irrespectively from the presence of DM (1st metatarsal head: p=0.02 Group 1 and Group 2 vs Group 3 and Group 4; 5th metatarsal head: p< 0.01 in Group 1 and Group 2 vs Group 3 and Group 4). Skin hydration score showed increased anhydrosis in both diabetics and severe obesity (p< 0.01 in Group 1 and Group 3 vs Group 2 and Group 4). Increase in thickness of skin and subcutaneous tissues was observed (at heel: p< 0.01 in Group 1 and Group 2 vs Group 3 and Group 4 and under the scaphoid p=0.03 Group 1 and Group 2 vs Group 3 and Group 4) and plantar fascia (in both regions p=0.02 Group 1 and Group 2 vs Group 3 and Group 4) in all obese patients, with or without DM.Conclusion: Severe obesity significantly affects both shape and structure of the foot, possibly exposing these patients to a higher risk of biomechanical stress. On such a background DM, modifying skin hydration and protective mechanisms exerts a synergistic role further increasing the risk of trauma and ulcers.Keywords: diabetes, obesity, skin disease